THE RELATIONSHIPS OF TAXONOMIC AND STRUCTURAL ATTRIBUTES ON ABOVE GROUND CARBON BIOMASS OF TROPICAL DRY FORESTS IN PHOU KHAO KHOUAY NATIONAL PARK, LAOS - Phomphoumy, Khamphet; Thi Thu Hien, Cao; Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2023)
Forest ecosystems play an integral role in climate regulation through carbon sequestration and storage. Tropical forests in Laos have undergone major degradation which threatened the standing biomass and carbon sequestration potential of these forests, apart from altering the dynamics of the ecosystem. In this study, species diversity and forest structure were assessed through 32 of 0.25-ha study plots representing 3 major forest types in Phou Khao Khouay Nation Park, Laos. The findings found a total of 5,477 individuals, 188 species belonging to 57 families. H. pierrei was the most dominant tree species (IVI =9.29%) among 138 species in DEF; A. grandis and L. fenestratus were the most co-domimant species (IVI=8.57%) among 126 species of MDF and P. merkusii covered the grestest IVI (20.02%) among 54 species in MCF. Individual tree distribution was inversed J-shape in all forest types suggesting good regeneration and recruitment potential. Significant differences of taxonomic and structural between 3 forest types showed through Kruskal-Wallis test with p-value < 0.05. Above ground carbon biomass decreased with decreasing species richness, basal area and volume through forest types, specifically 184.00±66.79 Mg/ha in DEF; 107.57±7.90 Mg/ha in MDF and 110.99±7.69 Mg/ha in MCF. Taxonomic and structural attributes contributed positive effects on above ground carbon biomass. Biodiversity conservation should be a key component of the UN Reducing Emission from Deforestation and Degradation strategy (REDD+).